Enhancing reliability of electricity supply of city electric networks cities of Dushanbe - Alexander Ivanovich Sidorov; Saidjon Tavarov (Institute of Advanced Engineering and Science, 2021)
The article is devoted to the actual problem of how to improve the reliability of the urban electric network. Based on the statistical analysis of the breakdown of electrical equipment in urban distribution networks in Dushanbe for the periods of 2017-2018 and for the reasons of damage leading to these emergency outages, the factors that affect the distribution of damage leading to emergency outages are identified. Taking into account the identified factors, a power consumption forecasting system is proposed that takes into account the local conditions of the city of Dushanbe. it allows us to suggest a way to control the operating parameters of the electric network, thereby increasing the reliability of the city's electric network in Dushanbe based on the recommendation of power consumption standards. Implementation of the control of the proposed method for improving the reliability of power supply to the urban electric network is proposed on the basis of the functionality of modern smart electricity metering using the control algorithm. To implement the control algorithm, schematic design for receiving and transmitting information from smart power metering to the data collection centre is proposed.